Porous orbital implant after enucleation in retinoblastoma patients: indications and complications. (2nd November 2018) - Lang, Paul; Kim, Jonathan W.; McGovern, Kathleen; Reid, Mark W.; Subramanian, Krishnan; Murphree, A. Linn; Berry, Jesse L.
ABSTRACT: This study aims to identify risk factors associated with complications in retinoblastoma patients following primary and secondary enucleations with porous implant placement. A retrospective case-control study was performed between 2010 and 2015. Data pertaining to subjects' demographics, medical history, clinical, and pathological findings, implant characteristics and complications were collected. The analysis included 103 eyes of 101 patients age 27.8 ± 21.9 months undergoing enucleation for retinoblastoma. Postoperatively, 19/103 (18%) eyes developed exposure, extrusion, or hematoma requiring subsequent surgery. Exposure was the most common postoperative complication (12/19, 63%). Age at enucleation 24 months or younger, Hispanic ethnicity, female gender, and intravenous chemotherapy prior to enucleation were associated with increased odds of implant complications. In contrast, patients who were given intravitreal melphalan (IM), subtenons carboplatin (SC), or external beam radiation therapy (EBRT) did not demonstrate an increased risk of complications. In this cohort of retinoblastoma patients undergoing primary or secondary enucleation with porous implants, implant exposure was the most common postoperative complication. Our findings suggest that female gender, Hispanic ethnicity, age at enucleation 24 months or younger, and intravenous chemotherapy prior to enucleation may increase the risk of complications.